Isolation ratio between the reflector antennas which have been had in the near-field region - Chekan, S. A. (Видавництво Національного університету "Львівська політехніка", 2009)
System from two one-mirror parabolic antennas, which are free situated in the nearfield zone are considered. The problem of transfer of capability from one antenna (active) to other antenna (passive) is solving. Results of numerical modeling depending on geometry of interaction antennas and their mutual position are resulted.
Keywords: reflector antenna; method physical opticians; a method of the geometrical theory of diffraction; interaction in a near-field region